Strengthening the Social Capital of the Blimbing Traditional Market Traders Association in Conflict Resolution Against the Malang City Government Market Revitalization Policy - Sulismadi, Sulismadi; Ishomuddin, Ishomuddin; Kartono, Rinikso; Wahyudi, Wahyudi (Technium Social Sciences Journal, 2023)
This study aims to analyze and describe the strengthening of the social capital of the Blimbing traditional market trader association in Malang City in conflict resolution against the market revitalization policy of the Malang City Government. Recently, the modernization of traditional markets has become one of the development agendas in every city. However, modernizing traditional markets tends not to favour the lower middle class and traditional traders as the main actors in traditional markets. Traditional traders are increasingly marginalized, and more modern traders replace their roles. In the case of conflict between Blimbing market traders and the Malang City Government, it was initiated because the policies issued by the Malang City Government were considered one-sided and detrimental to market traders. Even though the Malang City Government has made Project Agreement with Karya Indah Sukses.Co.Ltd, but the Blimbing market traders still refuse the revitalization project. This study uses a descriptive qualitative approach with a case study on the Blimbing traditional market in Malang City. The results showed that the revitalization policy of the Malang City Government had received resistance from the Association of Blimbing traditional market traders. But the, conflict resolution is carried out persuasively through; negotiation, mediation, and advocacy, in the hope of obtaining a mutually beneficial solution between the parties involved in the conflict. With the strengthening of social capital, the association of market traders succeeded in preventing the implementation of market development policies that could harm traders and received support and sympathy from various parties. In the end, the Malang City Government changed the policy direction by choosing alternatives to revitalize the development of the traditional market of Blimbing.